2017
DOI: 10.1103/physrevaccelbeams.20.112001
|View full text |Cite
|
Sign up to set email alerts
|

rf design of a pulse compressor with correction cavity chain for klystron-based compact linear collider

Abstract: We present an X-band high-power pulse compression system for a klystron-based compact linear collider. In this system design, one rf power unit comprises two klystrons, a correction cavity chain, and two SLAC Energy Doubler (SLED)-type X-band pulse compressors (SLEDX). An rf pulse passes the correction cavity chain, by which the pulse shape is modified. The rf pulse is then equally split into two ways, each deploying a SLEDX to compress the rf power. Each SLEDX produces a short pulse with a length of 244 ns an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…PET/MRI is a relatively new hybrid imaging modality that combines the functional information from PET with the high soft-tissue contrast provided by MRI [19]. This modality has shown promise in the assessment of various cancers, such as prostate, brain, and gynecological malignancies, and offers potential advantages over PET/CT in terms of reduced radiation exposure and improved soft-tissue visualization [20].…”
Section: Pet/mrimentioning
confidence: 99%
See 2 more Smart Citations
“…PET/MRI is a relatively new hybrid imaging modality that combines the functional information from PET with the high soft-tissue contrast provided by MRI [19]. This modality has shown promise in the assessment of various cancers, such as prostate, brain, and gynecological malignancies, and offers potential advantages over PET/CT in terms of reduced radiation exposure and improved soft-tissue visualization [20].…”
Section: Pet/mrimentioning
confidence: 99%
“…One of the main challenges in multimodal imaging is the accurate registration and fusion of images from different modalities [19]. Various factors can affect the quality of image registration, such as differences in patient positioning, scanner calibration, and image resolution [3].…”
Section: Challenges and Future Development Of Multimodal Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in pulse compressors [706] with super-compact spherical cavities has dramatically changed the performance potential for these systems. It has been shown that a chain of spherical cavities can produce tailored pulse formats with extremely high conversion efficiency if the power gain is kept low [711]. A pre-pulse power compression ratio of three can be achieved with >80% conversion efficiency.…”
Section: Future Programmementioning
confidence: 99%
“…Therefore, a cavity-based system can partly function like a delay line as an alternative. The idea is to put several resonant peaks around the operating frequency to simulate the delay line, which can be realized by coupled cavities or a cavity chain [25][26][27]. Such a system is expected to correct the pulse shape generated by a SLED or BOC type pulse compressor without need of low efficiency pulse modulation [20,28] or a solution based on long delay lines.…”
Section: Design Of Correction Cavity Chainmentioning
confidence: 99%